Comparison of the Quantiplex Version 3.0 Assay and a Sensitized Amplicor Monitor Assay for Measurement of Human Immunodeficiency Virus Type 1 RNA Levels in Plasma Samples - Highbarger, Helene C. (American Society for Microbiology, 1999)
This study evaluated correlation and agreement between version 3 of the Quantiplex human immunodeficiency virus type 1 (HIV-1) RNA assay (v3 branched DNA [bDNA]) and a sensitized Amplicor HIV-1 Monitor assay (reverse transcription [RT]-PCR) for the measurement of HIV RNA. Three hundred eighteen samples from 59 randomly selected, HIV-1-seropositive persons on various drug protocols from the National Institute of Allergy and Infectious Diseases HIV outpatient clinic were studied. The results indicate that v3 bDNA and RT-PCR are highly correlated (r = 0.98) and are in good agreement (mean difference in log(10) copies/ml ± 2 standard deviations = 0.072 ± 0.371). The relationship between values obtained by both assays is given by the following equation: log(10)v3 bDNA = −0.0915 + 1.0052 · log(10)RT-PCR. This represents a 1.026-fold difference between log(10)RT-PCR values and log(10)v3 bDNA values.